Kinematic Study of the effect of the orthosis in the internal rotation of the leg in a child with flexible flat foot - Pardos Barrado, Moisés; Sala Gutiérrez, Eduardo (Revista Internacional de Ciencias Podológicas, 2009)
For over a century plantar orthoses have been used for therapeutic purposes in different diseases of lower extremities, including the spine. The results of different treatments are successful in a high percentage as shown by numerous research papers. The scientific community has reflected the fact that different orthosis cause in the kinetics and kinematics with apparent profusion. Although there is great diversity in the objectives of the study, in the methods used and conclusions drawn, there is a widespread perception that admitting the undoubted success that orthosis involve large numbers of nosologic entities, it is more discussed the mechanism for its production. The physician has new technologies and new instruments available that can measure more objectively phenomena almost imperceptible by our senses. In this respect this work will research in the field of kinematics of the lower extremities treated with orthosis. The present work is focused on the study of a case of flatfoot in a child in our opinion provides qualitative considerations differentials that would explore new pathways of research.
Keywords: Gait analysis; Flat foot; Orthosis